CCAFS/FAO Expert Workshop on Smallholder Mitigation: Mitigation Options and Incentive Mechanisms. Rome, 7-8 July 2011. Workshop Summary - CGIAR Research Program on Climate Change, Agriculture and Food Security; Food and Agriculture Organization of the United Nations (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
The Workshop on Mitigation Options and Incentive Mechanisms was held on the identification of incentives for pro-poor smallholder-based mitigation. Its objective was to 1. Explore mitigation incentives to support smallholder livelihoods and food security, addressing: - Costs and benefits of mitigation options at the farm level and barriers for their adoption - Incentive mechanisms and associated institutional arrangements - Mechanisms specifically to reach women and the poor. 2. Develop principles for pro-poor incentives for smallholder farmers and 3. Identify priorities for actions and research.